A presença das Mulheres nos Conselhos Municipais de Pelotas - Mendes, Ana Cristina Lubke (2013)
This paper sought to investigate the presence of women in Municipal Councils of Pelotas, in order to identify factors that encourage women to participate in these spaces of discussion and deliberation of public policies. The general hypothesis is that specific features of the Councils encourage women to participate in these forums, in particular the form of representatives selection. The methodology used was documentary analysis and follow-up meetings to the questionnaires aplliance. The data confirmed the hypothesis that the Councils operation format, regarding how the female representatives are chosen, can act as a facilitator for the women presence in these participatory forums